On the occasion of raising the gay flag at city hall. - Sahl, Ted (photographer):::Creator::::::::::::
'Left to right are: Mayor Ron Gonzales, Mr. & Mrs. Ken Hayes, and Councilman Ken Yeager on the occasion of the gay flag being raised on the San Jose City Hall flag pole.